Vendor Financing - BRENNAN, MICHAEL J.; MAKSIMOVICs, VOJISLAV; ZECHNER, JOSEF (Journal of Finance, 1988)
ABSTRACT This paper shows that, even in the presence of a perfectly competitive banking industry, it is optimal for firms with market power to engage in vendor financing if credit customers have lower reservation prices than cash customers or if adverse selection makes it infeasible to write credit contracts that separate customers according to their credit risk. We analyze how the advantage of vendor financing depends on the relative size of the cash and credit markets, the heterogeneity of credit customers, and the number of firms in the industry.